1998
DOI: 10.1083/jcb.143.4.1067
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Role for Specific Spliced Variants of the α7β1 Integrin in Acetylcholine Receptor Clustering

Abstract: The clustering of acetylcholine receptors (AChR) on skeletal muscle fibers is an early event in the formation of neuromuscular junctions. Recent studies show that laminin as well as agrin can induce AChR clustering. Since the α7β1 integrin is a major laminin receptor in skeletal muscle, we determined if this integrin participates in laminin and/or agrin-induced AChR clustering. The alternative cytoplasmic domain variants, α7A and α7B, and the extracellular spliced forms, α7X1 and α7X2, were studied for their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 39 publications
3
72
0
Order By: Relevance
“…We therefore explored the hypothesis that VFDNFVLK binds to the ␣7␤1 integrin, better known as a laminin-1 receptor involved in neuromuscular (Burkin et al, 1998) and myotendinous (Crawley et al, 1997) junctions. Tenascin-C is enriched at neuromuscular and myotendinous junctions (Chiquet and Fambrough, 1984;Cifuentes-Diaz et al, 2002), colocalizing it with ␣7␤1.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore explored the hypothesis that VFDNFVLK binds to the ␣7␤1 integrin, better known as a laminin-1 receptor involved in neuromuscular (Burkin et al, 1998) and myotendinous (Crawley et al, 1997) junctions. Tenascin-C is enriched at neuromuscular and myotendinous junctions (Chiquet and Fambrough, 1984;Cifuentes-Diaz et al, 2002), colocalizing it with ␣7␤1.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] and exogenous LM-111 supplementation promotes acetylcholine receptor (AChR) clustering and functional NMJ formation in vitro. 7,21,38 LM and agrin can act together to enhance the number, size, and rate of AChR clusters. 38,39 LM also mediates the interaction between integrin α 7 β 1 and the neural AChR clusters on the muscle membrane, potentially stabilizing them and allowing them to be more readily innervated by the incoming neurite.…”
Section: Peripheral Nervous System Regenerationmentioning
confidence: 99%
“…7,21,38 LM and agrin can act together to enhance the number, size, and rate of AChR clusters. 38,39 LM also mediates the interaction between integrin α 7 β 1 and the neural AChR clusters on the muscle membrane, potentially stabilizing them and allowing them to be more readily innervated by the incoming neurite. 40 As a result, LM based neurogenic materials have been widely used as peripheral nerve grafts in several studies.…”
Section: Peripheral Nervous System Regenerationmentioning
confidence: 99%
“…The loss of this integrin subunit in lamb2 -/-may have an implication on the postsynaptic maturation of the NMJ. In support of this, in-vitro studies have demonstrated the role of integrins, particularly α7β1 in aggregation of AChR clusters which are dependent on laminins (Burkin et al, 1998;Burkin et al, 2000). Burkin et al (1998) showed that integrin α7β1 were colocalised to laminininduced AChR clusters but to a lesser degree to agrin-induced AChR clusters.…”
Section: Integrinsmentioning
confidence: 90%
“…These proteins include agrin, muscle specific receptor tyrosine kinase (MuSK) and rapsyn which play essential roles in the clustering of AChRs (Burden, 2002;Ghazanfari et al, 2011). Proteins that are localised at the postsynaptic membrane such as dystroglycan and integrins have also been suggested to be involved in the postsynaptic maturation of the NMJ (Burkin et al, 1998;Burkin et al, 2000;Nishimune et al, 2008). Podosomes, which are actin-rich organelles may also potentially assist in the maturation of the postsynaptic apparatus (Proszynski et al, 2009).…”
Section: Postsynaptic Regionmentioning
confidence: 99%